Mobile media, domestic play and haptic ethnography. (October 2017) - Richardson, Ingrid; Hjorth, Larissa
In this article, we explore the material, sensory and corporeal aspects of digital ethnography, primarily in the context of mobile media use in the domestic environment. We align our methodological approach to the 'sensory turn' in theory, situated loosely under the rubric of new materialism, and outline the insights that a post-phenomenological method can offer. Drawing from our current research into everyday media use conducted within Australian households, which involved a range of data collection methods aimed at capturing the embodiment of mobile media, we explore the significance of play in and around haptic interfaces. Mobile games are evidently integral to our embodied ways of knowing, and there are a number of challenges faced by the mobile media researcher who seeks to document, understand and interpret this contemporary cultural and everyday practice.